Changes in Tangible Social Support Over Time Among Older Adults Receiving Long-Term Services and Supports. (May 2023) - Goldman, Annika S.; Abbott, Katherine M.; Huang, Liming; Naylor, Mary D.; Hirschman, Karen B.
The purpose of this study was to examine changes in and predictors of perceived tangible social support over a 2-year period among older adults new to LTSS. Linear mixed effects models were used to model repeated measures of tangible social support as a function of LTSS type [NH, AL, HCBS], personal, clinical, and health-related quality of life variables. AL residents reported greater initial tangible social support, but NH and HCBS residents improved more over time. Predictors of increased tangible social support over time included greater positive affect, sense of aesthetics, education, satisfaction with family relationships, and total number of close friends and family. Decreased tangible support over time was associated with greater depressive symptoms. Findings indicate the positive influence of NH and HCBS services on perception of tangible social support, and the importance of addressing depressive symptoms and assisting with the maintenance of important relationships.